1960
DOI: 10.1161/01.res.8.5.934
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hypertension in the Dog Following Disruption of the Carotid Sinus Nerves and Subsequent Unilateral Renal Artery Constriction

Abstract: Constriction of 1 renal artery in combination with disruption of the carotid sinus nerves resulted in moderate chronic hypertension in dogs. Hypertension persisted at the same level in some of the animals after removal of the kidney 1 year later, while in others blood pressure decreased somewhat though not to the prehypertensive control level. Narrowing of 1 renal artery without carotid nerve disruption did not lead to significant chronic hypertension. Disruption of the carotid sinus nerves alone, on the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
3

Year Published

1964
1964
1980
1980

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
3
3
Order By: Relevance
“…" 17 In the present study of neurogenic hypertensive rats no positive correlation was observed between increases in pressure and increases in heart rate. The facts that these rats had intact all the efferent vagal fibers to the heart and that the heart rate in the rat is normally under almost maximal sympathetic tonus, 28 -M may partially explain why the unrestrained quiet denervated rats exhibited hypertension accompanied by normal heart rate.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…" 17 In the present study of neurogenic hypertensive rats no positive correlation was observed between increases in pressure and increases in heart rate. The facts that these rats had intact all the efferent vagal fibers to the heart and that the heart rate in the rat is normally under almost maximal sympathetic tonus, 28 -M may partially explain why the unrestrained quiet denervated rats exhibited hypertension accompanied by normal heart rate.…”
contrasting
confidence: 62%
“…" 17 In the rats of the present study no appreciable changes of pressure were observed after pure sinus denervation, but the elimination of only the aortic depressor fibers produced a transitory hypertension. Further work is necessary to assess whether there is really a predominance of the aortic over the sinus depressor fibers in the regulation of blood pressure in the rat.…”
contrasting
confidence: 43%
“…Other investigators have measured an increase in the magnitude of renal hypertension following partial or total sinoaortic deafferentiation (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…They could not incriminate the depressed baroreflex sensitivity as a cause of hypertension in patients with chronic renal failure. Thus although baroreceptor dysfunction does not by itself appear to cause persistent hypertension in chronic renal failure, denervation of baroreceptors has been found by some workers (Kezdi, 1960; Lawrence & Dickinson, 1964) to augment renal hypertension or at least to accelerate the rise of pressure (Liard, Cowley, McCaa, McCaa & Guyton, 1974;Cowley & Guyton, 1975).…”
Section: Osamu Tomiyarna Et Almentioning
confidence: 98%
“…Motor nerve conduction velocity was measured on the ulnar nerve (Kitaoka, 1976). Its normal range is more than 49 m/s.…”
Section: Serum Creatinine Concentrations Were Measured With An Autoanmentioning
confidence: 99%